Heat shock protein 90 localizes to the surface and augments virulence factors of Cryptococcus neoformans. - Sharanya Chatterjee; Utpal Tatu (Public Library of Science (PLoS), 2017)
Thermotolerance is an essential attribute for pathogenesis of Cryptococcus as exemplified by the fact that only two species in the genus, which can grow at 37°C, are human pathogens. Species which have other virulence factors including capsule formation and melanisation, but lack the ability to propagate at 37°C are not pathogenic. In another related fungal pathogen, Candida albicans, heat shock protein 90 has been implicated to be a central player in commanding pathogenicity by governing yeast to hyphal transition and drug resistance. Exploring Hsp90 biology in Cryptococcus in context of thermotolerance may thus highlight important regulatory principles of virulence and open new therapeutic avenues.Hsp90 is involved in regulating thermotolerance in Cryptococcus as indicated by growth hypersensitivity at 37°C upon mild compromise of Hsp90 function relative to 25°C. Biochemical studies revealed a more potent inhibition of ATPase activity by pharmacological inhibitor 17-AAG at 37°C as compared to 25°C. Catalytic efficiency of the protein at 37°C was found to be 6.39×10-5μM-1. Furthermore, indirect immunofluorescence analysis using a specific antibody revealed cell surface localization of Hsp90 via ER Golgi classical secretory pathway. Hsp90 was found to be induced under capsule inducing conditions and Hsp90 inhibition led to decrease in capsular volume. Finally compromising Hsp90 function improved anidulafungin tolerance in Cryptococcus.Our findings highlight that Hsp90 regulates pathogenicity of the fungus by myriad ways. Firstly, it is involved in mediating thermotolerance which implies targeting Hsp90 can abrogate thermotolerance and hence growth of the fungus. Secondly, this study provides the first report of biochemical properties of Hsp90 of a pathogenic fungus. Finally, since Hsp90 is localised at the cell wall, targeting cell surface Hsp90 can represent a novel strategy to combat this lethal infection.